2009
DOI: 10.1002/chem.200901152
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism of Electrocyclic Ring‐Opening of Diphenyloxirane: 40 Years after Woodward and Hoffmann

Abstract: The photochemistry of diphenyloxirane has been investigated by using static density functional theory and first-principles molecular dynamics. We optimised potential-energy surfaces for both the disrotatory and the conrotatory pathway in the first excited state. Although the disrotatory pathway does not seem to be favoured energetically, we get only the disrotatory product during the molecular dynamics simulations. This can be attributed to the "on-the-fly" description of the electronic structure in a first-pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
25
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
4
1
1

Relationship

2
4

Authors

Journals

citations
Cited by 19 publications
(26 citation statements)
references
References 25 publications
1
25
0
Order By: Relevance
“…As a consequence, the elimination of SO 2 results in a biradical BR2 with a conformation that is unfavorable for oxirane formation, but enables efficient hydrogen migration to result in aldehyde 3a . Theoretical calculations have confirmed that acetaldehyde derivatives may be formed upon rearrangement of the 1,3-oxyethandiyl [2021] and that a subsequent decarbonylation results in an alkyl radical. The latter reaction yields bibenzyl ( 4 ) and toluene ( 7 ) in the photoreaction of 8 .…”
Section: Resultsmentioning
confidence: 99%
“…As a consequence, the elimination of SO 2 results in a biradical BR2 with a conformation that is unfavorable for oxirane formation, but enables efficient hydrogen migration to result in aldehyde 3a . Theoretical calculations have confirmed that acetaldehyde derivatives may be formed upon rearrangement of the 1,3-oxyethandiyl [2021] and that a subsequent decarbonylation results in an alkyl radical. The latter reaction yields bibenzyl ( 4 ) and toluene ( 7 ) in the photoreaction of 8 .…”
Section: Resultsmentioning
confidence: 99%
“…This approach has been used previously to describe photoreactions both in the gas phase and in the condensed phase, see for example refs. [28,29]. For these calculations the CPMD code [30] was employed with the BLYP density functional [31,32] and Troullier-Martins pseudopotentials [33] with a plane wave cutoff of 70 Rydberg.…”
Section: Methodsmentioning
confidence: 99%
“…It has been shown previously, that it is not always possible to decide between different reaction paths solely on the basis of energy differences. [21] During the course of any reaction, the wavefunction has to change continuously in time, because otherwise it would not be differentiable with respect to time and thus violate a fundamental principle of quantum mechanics. Therefore the determination of the reaction mechanism may depend crucially on the evolution of the wavefunction.…”
mentioning
confidence: 99%